PERCEPTION OF TEACHERS TOWARDS TEACHER PERFORMANCE APPRAISAL AND ITS EFFECT ON SCHOOL ACADEMIC PERFORMANCE IN TRANS-NZOIA COUNTY, KENYA - Chepkoech, Emily (IJRDO-Journal of Applied Science, 2015)
The study sought to investigate the perception of teachers towards teacher performance appraisal and its effect on school academic performance. It is based on Duncan (1983) theory of management by objective (MBO). The study employed a descriptive survey design with a target population of all head and all teachers of the 83 public secondary schools in TransNzoia County. The study used stratified sampling technique to sample 36 public secondary schools out of 83 in the whole district from boys, girls and mixed secondary schools. Finally, simple random sampling was used to select 36 head teachers and 4 teachers from each selected schools. This represented a sample of over 43% of the target population. However, only 30 schools returned the questionnaires which were used in data collection. Data was analyzed using descriptive statistics in form of tables, graphs and charts to answer the question of the study. A pilot study was carried out to test the reliability of the research instrument. Then study findings revealed that performance appraisal exists in schools and that it contributes to effective school management in achieving desired academic performance. The study findings would benefit educational planners, human resource officers, teachers, management and teachers service commission on how to manage performance appraisal effectively. The study recommends that performance appraisals ought to be professionalized, appraisers to be thoroughly inducted on appraisal techniques as well as returning performance appraisal feedback to appraises promptly.